The microeconomics of inequality, poverty and market liberalizing reforms - Rafael E. de Hoyos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper illustrates how the use of microeconometric techniques can be used to uncover the micro dynamics behind macro shocks. Using Mexican micro data we find out that—controlling for everything else—between 1994 and 1998 returns to personal characteristics in the tradable sector increased particularly those of skilled labourers. By the year 2000 the positive shock upon the tradeable sector vanishes with returns to personal characteristics converging to the levels observed in the non-tradable sector. We use our model's results to simulate a scenario where the Mexican economy experienced the negative shock of the peso crises in the absence of trade liberalization (NAFTA) and find out that under such a scenario the poverty headcount ratio would have increased more than 2 percentage points above the one observed in 1996. The simulated second order effect of these changes shows that the skill mixed changed in a way that favoured relatively skilled men and relatively unskilled women. These changes in labour participation and occupation had an overall positive income effect though adverse in distributive terms. – inequality ; poverty ; microsimulation ; NAFTA ; Mexico
Keywords: C3; D1; F16; O24; 330; Mikroökonometrie; Haushaltseinkommen; Einkommensverteilung; Außenwirtschaft; Wirtschaftswachstum; Mexiko